Effects of insect and decapod exclusion and leaf litter species identity on breakdown rates in a tropical headwater stream - Rincón, José (2014)
High species richness of tropical riparian trees influences the diversity of organic detritus entering streams, creating temporal variability in litter quantity and quality. We examined the influence of species of riparian plants and macroinvertebrate exclusion on leaf-litter breakdown in a headwater stream in the Luquillo Mountains of Puerto Rico. Leaf litter ofDacryodes excelsa (Burseraceae), Guarea guidonia (Meliaceae), Cecropia scheberiana (Moraceae), Manilkara bidentata (Sapotaceae), and Prestoea acuminata (Palmae) were incubated in litter bags in a pool of Quebrada Prieta. Fine mesh bags were used to exclude macroinvertebrates during leaf breakdown, and coarse mesh bags allowed access to decapod crustaceans (juvenile shrimps and crabs) and aquatic insects (mainly mayflies, chironomids, and caddisflies). D. excelsa and G. guidonia (in coarse- and fine-mesh bags) had significantly higher breakdown rates than C. scheberiana, M. bidentata, and P. acuminata. Breakdown rates were significantly faster in coarse-mesh bag treatments for all leaf types, thus indicating a positive contribution of macroinvertebrates in leaf litter breakdown in this headwater stream. After 42 days of incubation, densities of total invertebrates, mayflies and caddisflies, were higher in bags with D. excelsa and G. guidonia, and lower in P. acuminata, C. scheberiana y M. bidentata. Decay rates were positively correlated to insect densities. Our study highlights the importance of leaf identity and macroinvertebrate exclusion on the process of leaf litter breakdown in tropical headwater streams. Rev. Biol. Trop. 62 (Suppl. 2): 143-154. Epub 2014 April 01.